Powertrain Design and Simulation for an Electric Go-Kart - Aiman Omar,; Haziq Zull Azri,; Siti Nuraisyah Sairan,; Mohamad, Mahmod Abd Hakim; Mohd Faisal Hushim,; Yahaya Ramli, (Multidisciplinary Applied Research and Innovation, 2023)
Replacing fuel with electric would be better for the environment as fuel, which has been widely used as main sources of energy, contributes to the world carbon footprint and it is increasing per billions over the year. To overcome this, electric powered go-kart’s powertrain is developed from DC motor and DC batteries. Simulation and 3D printing is involved to find the best configuration for the powertrain and the performance of the powertrain is also tested. For this project, 16 packs of 3.2V LiFePO4 batteries, a 48V DC2000W brushless motor, a motor controller and a battery management system are used and mounted on a go-kart chassis. CAD model of the powertrain is designed in a smaller scale and is simulated before rapid prototyped to test the integration of the powertrain in a smaller scale to reduce the cost of error. It is found that the powertrain can run for 30 minutes using full power without any damage to the components and no sign of overheating with decreasing of 0.6V per 10 minutes. In conclusion, this research aims to provide the sources needed to overcome carbon footprint caused by fuel by using electricity. In addition, all the objective of this project are met and suggestion for future work is to test the real performance of the powertrain with track testing.